Inhibition of Androgen Receptor Expression with Small Interfering RNA Enhances Cancer Cell Apoptosis by Suppressing Survival Factors in Androgen Insensitive, Late Stage LNCaP Cells - Sang Soo Kim; Hee Joo Cho; Jung Yoon Kang; Hee Kyu Kang; Tag Keun Yoo (The Scientific World Journal)
Introduction.The aim was to evaluate the changes of androgen receptor (AR) expression quantitatively and to identify influence of AR on cancer related survival markers in LNCap cell line. Materials and Methods. We compared expressions of AR, heat shock protein 27 (HSP27), clusterin (CLU), glucose-related protein 78 (GRP78), and cellular FLICE-like inhibitory protein (c-FLIP) and their genes between es-LNCaP (less than 33 times subcultured, L-33), ls-LNCaP (over 81 times subcultured, H-81), and si-LNCaP (AR siRNA transfected ls-LNCaP) by Western blotting and RT-PCR. Results. The expressions of AR, HSP27, CLU, GRP78, and c-FLIP were increased in ls-LNCaP compared with es-LNCaP (AR, 157%; HSP27, 132%; CLU, 146%; GRP78, 138%; c-FLIP, 152%). However, in si-LNCaP cell line, protein expressions were reversed to the level of es-LNCaP cell lines (25, 102, 109, 98, and 101%), and gene expressions on real-time PCR were also reversed to the expression level of es-LNCaP (ls-LNCaP: 179, 156, 133, 123, and 167%; si-LNCaP: 22, 93, 103, 112, and 107%). Conclusions. This finding suggests that androgen receptor can be related to the increased expression of cancer related survival markers such as HSP27, GRP78, CLU, and c-FLIP in late stage prostate cancer, and also inhibition of AR gene can be a therapeutic target in this stage of cancer.